WOMEN ON BOARD (WOB) DAN RISK TAKING PADA BANK PERFORMANCE (STUDI KASUS PADA BANK UMUM KONVENSIONAL PERIODE 2017-2020) - Mahirun Mahirun; Anggrainy Putri Ayuningrum; Widya Arsyida (LPPM Universitas Pekalongan, 2022)
Bank have a function as financial intermediary so that bank become bridge for saving and providing credit. These main activities have credit risk which represented by Non Performing Loan (NPL) and liquidity risk represented by Loan to Deposit Ratio (LDR). The management of bank is carried out by board of directors who consiststing of various gender, region, education, etc. Gender diversity on bank represented by Women on Board (WOB). The purpose of this research is to determine Non Performing Loan (NPL), Loan to Deposit Ratio (LDR), and Women on Board to Return on Assets (ROA) in banks listed on the Indonesia Stock Exchange in 2017-2020 use several criteria. This study uses multiple linear regression analusis method using SPSS version 24. The results of this research state that NPL has negative and significant effect on ROA. LDR has positive and not significant effect on ROA. WOB has negative and not significant effect on ROA. Size as control variable has a positive and significant on ROA.